Improvement of Thermal and Morphological Properties of Nitrile Rubber by Radiation Vulcanization - سلامة محمد علي; عجي زكي; مخلوف أحمد (Latakia University Journal -Engineering Sciences Series, 2020)
Radiation vulcanization of nitrile butadiene rubber composites containing different percentages of carbon black was carried out using gamma Radiation at doses up to (300 KGy). The results of this study also showed a decrease in the percentage of swelling of the composites prepared in the hydraulic and engine oils, with the increase in radiation dose and also with the increase in loading with black carbon. but this swelling ratio increased slightly to increase the temperature of the studied oil. The results of the thermal analysis of the composites showed an increase in the glass transition temperature with increase in the irradiation dose as a result of the radiation-induced crosslinking that restricts the freedom of movement of nitrile rubber chains. The effect of the irradiation dose on the amount of abrasion of the composites was also studied by measuring the size of the abrasive part of the material, and it was found that the abrasion resistance increases by increasing the irradiation dose up to (150 KGy) and then decreasing.